PENINGKATAN PARTISIPASI MASYARAKAT DALAM KEGIATAN DONOR DARAH DI PALANGKA RAYA - Teguh Pribadi; Asro' Laelani Indrayanti; Elyta Vivi Yanti (Universitas Islam kalimantan MAB, 2017)
The purpose of the blood donation social devotion program were: 1) to assisted the Blood Donor Unit of The Indonesian Red Cross (UTD-PMI) increased blood reserves to fulfil the blood needs in Palangka Raya city, 2) to socialized blood donation activities on the Universitas PGRI Palangka Raya (UPP) for the communities in and around the campus. Blood donation social activities were attended by 99 participants from students of police school (SPN), students, UPP Lecturers, university student organisation board (BEM), student regiment (Menwa), and the general public. By sex participants of this activity were dominated by men (73 people) and the women (26 people). The amount of blood bags that can be collected during this activity were 69 blood bags. Blood donation activities that are attractively packaged, publicized, and involving organizations/institutions can increase the level of community participation.